Impacted fetal head: A retrospective cohort study of emergency caesarean section. (June 2021) - Cornthwaite, Katie; Draycott, Tim; Bahl, Rachna; Hotton, Emily; Winter, Cathy; Lenguerrand, Erik
Highlights: Impacted fetal head at caesarean section is almost as common as shoulder dystocia. Impacted fetal head is as common in caesarean sections prior to, as at full cervical dilatation. Complications of impacted fetal head are independent of those of second-stage caesarean. Impacted fetal head at caesarean section is variably managed within UK maternity units. Junior obstetricians are more likely to diagnose an impacted fetal head than consultants. Abstract: Objective: To investigate risk factors, management and outcomes of impacted fetal head (IFH) at caesarean section (CS). Study design: This is a retrospective cohort study of all women with singleton, cephalic pregnancies who had an emergency CS during one-year (2016) at North Bristol NHS Trust, UK (n = 838). The incidence of caesarean section at full dilatation (CSFD) and IFH were calculated using the annual birth rate. To identify risk factors for IFH, maternal, perinatal and intrapartum characteristics were compared according to the presence or absence of IFH, and separately for first- and second-stage CS. Techniques employed to disimpact the fetal head were described. Univariable and multivariable comparisons of maternal and perinatal outcomes were made between cases with and without an IFH. Characteristics and outcomes were compared using modified Poisson regression. Results: CSFD accounted for 2.1 % of all births. IFH complicated 1.5 % of all births (11.3 % of emergency CS), with 55.8 % occurring prior to full cervical dilatation. Increased rates of IFH at CS were associated with: oxytocin augmentation (RR = 2.47 [1.61–3.80]), full cervical dilatation (RR = 4.24 [2.96–6.07], mid/low station (RR = 4.14 [2.72–6.32]), moulding (RR = 4.39 [2.55–7.54]) and caput (RR = 6.60 [3.09–14.10]). Junior operators documented IFH more than consultants (RR = 9.61 [1.35–68.2]). The strategies recorded for managing IFH included: tocolysis, reverse breech extraction and vaginal push up (33.7 %, 14.7 % and 11.6 % cases respectively) with two or more techniques used in 21.1 % cases. IFH at CS was independently associated with an increased risk of uterine extensions (RR = 3.09 [1.96–4.87]) and a composite adverse perinatal outcome (RR = 1.66 [1.21–2.28]). Conclusions: IFH is a common and heterogeneous complication associated with increased complications for both mother and baby, independent of those of CSFD. Obstetricians must remain vigilant to the possibility of IFH at all emergency CS, particularly those at full cervical dilatation or with evidence of obstructed labour. There is an urgent need for a standardised management algorithm and training in evidence-based disimpaction techniques.